2022
DOI: 10.1155/2022/4688689
|View full text |Cite|
|
Sign up to set email alerts
|

Meta-Analysis of Different Acupuncture Points in the Treatment of Ankylosing Spondylitis with Supervised Moxibustion

Abstract: Objective. To investigate the clinical efficacy of different acupuncture points in the treatment of ankylosing spondylitis with supervised moxibustion. Methods. Retrospective analysis of 61 AS patients (diagnosed as ankylosing spondylitis of kidney-yang deficiency type by Chinese medicine) admitted to our hospital from January 2020 to February 2021, randomly divided into 30 cases in the experimental group (Du moxibustion + basic western medicine treatment) and 31 cases in the control group (basic western medic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%